Searchable talk as discourse practice on the internet: The case of "#bindersfullofwomen". (June 2016) - Zhu, Hongqiang
Abstract: This paper examines the phrase #bindersfullofwomen as an example of searchable talk in the microblogging sphere of Twitter. The data were collected and sampled in terms of its temporal development on Twitter. Drawing on the content analysis combined with descriptive statistics, the paper identified and compared the Twitter users as Journalist users and Ordinary users who are engaged with Twitter communication. It shows that Journalists tend to initiate the topic at the early stage of communication. Soon afterwards, the Ordinary participants dominate the Twitter communication. The tweets are textually characterized into three different categories on the formal grounds: Hashtags, Hashtags plus texts and anything with a link" or "a retweet", in the heteroglossic context of micro-blogging sphere. The categorization of tweets contributes as a methodology to distinguish the discourse practice performed by different Twitter users. The results show that both Journalist and Ordinary favor to post the informative tweets throughout the sampled period. The quantity of interactive tweets is becoming less favorable; however, in contrast, the tweets on the indeterminate plane gain high popularity from the early phase of the period. Our comparison indicates that the boundary between Journalist and Ordinary seems to be indistinct in terms of their contents. Highlights: We distinguish and compare two groups of Twitter users (i.e., Journalist vs. Ordinary) who are engaged with the political communication. We picture the scenarios (i.e., the general trend of communication and the categorization of the tweets) of the discourse practiced by the two groups in political communication during the sampled time period. There is a contrast between Journalist and Ordinary at the early stage of Twitter communication. There is blurring tendency between Journalist and Ordinary in terms of the contents of tweets.